pengaruh Kepemilikan Manajerial, Struktur Modal dan Investment Opportunity Set (IOS) Terhadap Kualitas Laba - Umammi, Safira; Azzahra, Khoirunnisa (LPPM Universitas Putera Batam, 2024)
This research aims to provide empirical evidence on the influence of the independence of Managerial Ownership, Capital Structure, Investment Opportunity Set on Profit Quality in consumer non-cylicals sector companies lister on the Indonesia Stock Exchange for the 2018-2022 period. The number of research samples is 15 consumer non-cylicals sector companies. Which is determined based on the purposive sampling method. The Methods used are multiple linear regression model analysis, common effect model selection test, classical assumption test, multiple linear test and hypothesis testing with the helm of statistical data processing e-views versin 12. Research results this shows thas Managerial Ownership, Capital Structure, Investment Opportunity Set simultaneously have a significant effect on Earnings Quality and the t test states that Capital Structure has a significant effect on Earnings Quality, on the Managerial Owneship variable, Investment Oppourtunity Set does no have significatnt effect on Earnings Qualtiy.